Amphora types of Magdalensberg - Tamas Bezeczky (Arheološki Vestnik, 1998)
The economic and political role of the Magdalensberg settlement is well-known. The Mediterranean food products transported and stored in the amphorae were primarily consumed by the Italian merchants. The stamps and inscriptions of the amphorae refer to Italian, Istrian, Spanish, southern France and Greek centres of the production. However, in order to have a more balanced view, the amphorae without inscriptions also have to be considered. This paper is primarily concerned with the typology of the Magdalensberg amphorae.